Медійна історія та професійна репутація історика - Удод, О. (Історіографічні дослідження в Україні, 2020)
У статті проаналізовано нові умови, у яких розгортається наукова діяльність сучасних істориків. Інформаційна революція, бурхливий розвиток інформаційно-комунікаційних технологій та цифрової історії суттєво змінили вимоги до професії історика: він стає публічним, оволодіває інформаційною компетентністю, відповідає на виклики медіатизації історії. Соціальна і професійна репутація історика, його символічний капітал, взаємини з державними і науковими інституціями напряму залежать від уміння ефективно працювати у медіатизованому середовищі. Обґрунтовується необхідність дискусій в науковому середовищі щодо професійного стандарту історика та його власної ідентичності, здатності історика виконувати важливу суспільну функцію діалогу сучасності з минулим. The article analyzes the new conditions in which the scientific activity of modern historians unfolds. The information revolution, the rapid development of information and communications technologies and "digital" history have significantly changed the requirements for the profession of historian: he becomes public, acquires information competence, responds to the challenges of mediatization of history. The social and professional reputation of the historian, his symbolic capital, relations with state and scientific institutions directly depend on the ability to work effectively in a mediated environment. The necessity of discussions in the scientific environment on the professional standard of the historian and his own identity, the ability of the historian to perform an important social function of the dialogue of the present with the past is substantiated.